Emerging therapies in Friedreich's ataxia. (February 2016) - Aranca, Tanya V; Jones, Tracy M; Shaw, Jessica D; Staffetti, Joseph S; Ashizawa, Tetsuo; Kuo, Sheng-Han; Fogel, Brent L; Wilmot, George R; Perlman, Susan L; Onyike, Chiadi U; Ying, Sarah H; Zesiewicz, Theresa A
Friedreich's ataxia (FRDA) is an inherited, progressive neurodegenerative disease that typically affects teenagers and young adults. Therapeutic strategies and disease insight have expanded rapidly over recent years, leading to hope for the FRDA population. There is currently no US FDA-approved treatment for FRDA, but advances in research of its pathogenesis have led to clinical trials of potential treatments. This article reviews emerging therapies and discusses future perspectives, including the need for more precise measures for detecting changes in neurologic symptoms as well as a disease-modifying agent.